2018
DOI: 10.3892/ol.2018.8113
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a murine breast tumor model by subcutaneous or orthotopic implantation

Abstract: A number of murine models are used to mimic the pathology of breast cancer. Tissue inoculation and cell inoculation using orthotopic implantation (OS) and subcutaneous implantation (SQ) are commonly used to generate murine models to investigate cancer. However, limited information is available in regard to the variations of these methods. The present study compared growth, metastasis, survival and histopathology of tumors produced using OS and SQ to characterize features of the tumors produced by the two disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…A total of 30 female BALB/c mice (age, 6-8 weeks; weight, 18±2 g) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Beijing, China), and housed under specific pathogen-free conditions at a constant temperature (20±2°C) and 40-50% humidity in a 12-h light/dark cycle with free access to food and water. The 4T1 orthotopic mammary tumor model was established as previously described ( 41 , 44 ). Briefly, 1×10 4 4T1 cells were injected into the left fourth mammary fat pad during isoflurane gas anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 30 female BALB/c mice (age, 6-8 weeks; weight, 18±2 g) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Beijing, China), and housed under specific pathogen-free conditions at a constant temperature (20±2°C) and 40-50% humidity in a 12-h light/dark cycle with free access to food and water. The 4T1 orthotopic mammary tumor model was established as previously described ( 41 , 44 ). Briefly, 1×10 4 4T1 cells were injected into the left fourth mammary fat pad during isoflurane gas anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that a relation between tumor volume and radiotracer uptake was demonstrated in subcutaneous xenograft models but not in the orthotopic model. As already reported by several studies, the microenvironment of orthotopic implantation may be more favorable to tumor development [26]. In a second time, we performed the evaluation of early response to paclitaxel by [ 18 F]ML-10 and [ 18 F]FDG PET imaging on MDA-MB-468 xenograft models.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the malonic acid moieties of this radiotracer have pKa values of 3.07 and 5.78. At physiological pH, the di-anionic form of malonate predominates [20,26,[28][29][30]. According to pKa values cited, a decrease of extracellular pH will favor the apparition of the mono-protonated carboxylic acid form of [ 18 F]ML-10 and facilitate its interaction with the membrane of the apoptotic cells [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be accurately detected in vivo without killing mice [6] . Zhang et al [7] found that the results of in vivo imaging and pathological detection are consistent, but compared with HE staining, the growth and metastasis of breast cancer can be more directly and clearly observed using in vivo imaging system. In vivo imaging method is applied to study transplanted tumor in mice.…”
Section: Introductionmentioning
confidence: 98%